FUNCTIONAL POLYMORPHISMS IN NRF2: IMPLICATIONS FOR HUMAN DISEASE - Cho, Hye-Youn (Free Radic Biol Med, 2015)
Nuclear factor (erythroid derived)-2 like 2 (NFE2L2), also known as nuclear factor erythroid 2 (NF-E2)-related factor 2 (NRF2), is a ubiquitous transcription factor essential for protecting cells and tissues from oxidative stress-induced injury. Positional cloning and studies with Nrf2 knockout mice have identified important roles for this transcription factor in disease phenotypes for many organ systems. Studies have also characterized the means through which human NRF2 is regulated and the mechanisms of interaction with antioxidant response elements (ARE) in promoters of effector genes. Moreover, single nucleotide polymorphisms (SNPs) in NRF2 have been identified and evaluated for effects on gene expression and function, and translational investigations have sought to determine whether loss of function SNPs associate with disease progression. In this review, we present 1) an overview of the human NRF2 gene and protein domain, 2) identification of genetic mutations in NRF2 and associations of the mutations with multiple diseases, and 3) the role of somatic mutations in NRF2 in diseases, primarily various cancers.